Vegetation analyses of Sebangau peat swamp forest, Central Kalimantan - EDI MIRMANTO (Biodiversitas Journal of Biological Diversity, 2010)
Mirmanto E (2010) Vegetation analyses of Sebangau peat swamp forest, Central Kalimantan. Biodiversitas 11: 82-88. The vegetation analysis study has been made in Sebangau peat-swamp forest, Central Kalimantan. Eight permanent plots of 50-m x 50-m were set-up distribute from close to the river with shallow peat-layer up to the inland with relatively deep peat-layer. Enumeration of trees (GBH > 15 cm) was conducted in all of 8 plots. Overall there are 133 species (taxa) were recorded within 8 plots belong to 34 families where Dipterocarpaceae, Clusiaceae, Myrtaceae and Sapotaceae were the most dominant family. Out of all species recorded, Combretocarpus rotundatus, Palaquium leiocarpum, Stemonurus scorpioides and Tristania whittiana were the most dominant species. Two community’s types namely Combretocarpus rotundatus-Shorea balangeran community and Palaquium leiocarpum-Eugenia densinervium communitywere recognized and they distributed in slightly different habitat condition. The sequence of these two communities’ shows significantly related to both distances to river and peat-depth. In addition there was indication the presence of habitat preference among tree species.Key words: vegetation, peat-swamp, community, Sebangau, Central Kalimantan